Analisa Tingkat Kepuasan Pengguna Website Badan Kepegawaian, Pendidikan, Dan Pelatihan Daerah Pemerintah Kabupaten Boyolali Menggunakan Metode End User Computing Satisfaction - Agustiningsih, Yuliana; Harjanto, Sri; Setiyowati (Redtech Putra Benua, 2024)
The Boyolali District Civil Service, Education, and Training Agency (BKP2D) serves as a platform for exchanging information with Civil Servants (PNS) in Boyolali Regency. The Boyolali Regency Government continuously develops and improves the website to ensure the quality and satisfaction of its users. However, the level of user satisfaction with the BKP2D website among its users is not yet known. Therefore, the End User Computing Satisfaction (EUCS) method is employed to determine the extent of user satisfaction with the website. This method involves measuring variables that encompass content, accuracy, format, ease of use, and timeliness. The BKP2D website for Boyolali Regency can be accessed at http://bkp2d.boyolali.go.id/. The research was conducted by distributing questionnaires through Google Forms to 379 respondents. The data from the questionnaires were processed using SPSS for descriptive statistical analysis. The research results indicate an average score of 3.29 (satisfied), which means that users generally find the BKP2D website satisfactory